Baker, Herbert (Sir) 1901. Renovated design for Craigleith. Plan. West and north elevations. Side facade. - Baker, Herbert (Sir) (My University, 2011)
Baker, Herbert (Sir) 1901. Renovated design for Craigleith. Plan. West and north elevations. Side facade. (3x pencil and watercolour paint on paper)
Baker, Herbert (Sir) 1901. Renovated design for Craigleith: Plan: pencil and watercolour paint on paper 126x210. West and north elevations: pencil and watercolour paint on paper 126x210. Side facade: pencil and watercolour paint on paper 133x85.
Keywords: Baker, Herbert (Sir) 1901. Renovated design for Craigleith. Plan. West and north elevations. Side facade.